Measles vaccine coverage among children born to Somali immigrants in Norway - Sherin Marie Jenness; Preben Aavitsland; Richard Aubrey White; Brita Askeland Winje (BMC, 2021)
Abstract Background Despite overall good vaccination coverage in many countries, vaccine hesitancy has hindered full coverage and exposed groups to the risk of outbreaks. Somali immigrant groups have been known to have low measles vaccination coverage, leading to outbreaks in their communities. Current research indicates a general lack of trust in the healthcare system, the use of alternative information sources and inadequate health literacy can be contributing factors. We explore measles vaccine coverage in children born to Somali parents in Norway, whether it has changed over time and factors that may influence coverage. Methods Data was extracted from the National Population Register on all children born in Norway from 2000 to 2016, where both parents originated from Somalia. Date of birth, gender, residential area at birth and date of immigration and emigration for both parents was linked to information on measles vaccination from the National Immunisation Register. Results We found that children born to Somali immigrants in Norway had suboptimal measles vaccine coverage at 2 years; for children born in 2016 the coverage was 85%. Coverage declined between 2000 and 2016, and at a greater rate for boys than girls. Children born to mothers residing in Norway for 6 years or more had lower coverage compared to those with mothers residing less than 2 years prior to their birth. Children born in the capital and surrounding county had significantly lower coverage than children born elsewhere in Norway. Discussion New targeted interventions are needed to improve measles vaccine coverage among Somali immigrants in Norway. Some possible strategies include using Somali social media platforms, improving communication with Somali parents and tighter cooperation between various countries' vaccination programmes.